Analisis Determinan Indeks Pembangunan Manusia di Indonesia Tahun 1990-2021 - Nurlina, Nurlina; Ridha, Ahmad; Asnidar, Asnidar (Fakultas Ekonomi Universitas Samudra, 2023)
The purpose of this study is to analyse the determinants of the human development index in Indonesia. The variables analyzed include economic growth, government spending on education and the inflation rate. The data period is 1990-2021, with the analysis method using the autoregressive distributed lag (ARDL) model. The results obtained show that economic growth and government spending have a positive and significant effect on HDI in both the long and short term, while inflation has a negative and significant effect on HDI. The theoretical implication is that there is a need for stable economic growth and increased spending on education to support an increase in people's welfare as reflected in the increase in the HDI value. In addition, the government needs to control the inflation rate more effectively.